Moving media and conflict studies beyond the CNN effect. Issue 4 (3rd March 2016) - Gilboa, Eytan; Jumbert, Maria Gabrielsen; Miklian, Jason; Robinson, Piers
Abstract: After the 'CNN effect' concept was coined two decades ago, it quickly became a popular shorthand to understand media-conflict interactions. Although the connection has probably always been more complex than what was captured in the concept, research needs to be updated in order to better understand the multifaceted contemporary environments of both media and conflict. There are growing numbers and types of media sources, and multiple interactions between media and conflict actors, policymakers and engaged publics from the local to the global and back. We argue that understanding the impact of media reporting on conflict requires a new framework that captures the multilevel and hybrid media environments of contemporary conflicts. This study provides a roadmap of how to systematically unpack this environment. It describes and explains how different levels, interactions, and forms of news reporting shape conflicts and peacebuilding in local, national and regional contexts, and how international responses interact with multiple media narratives. With these tools, comprehensive understandings of contemporary local to global media interactions can be incorporated into new research on media and conflict.